Does Type of Fraudulent Act Have an Impact On Whistleblowing Intention? - Caesar Marga Putri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
The purpose of this research is to examine empirically the impact of two types of fraudulent act on individual’s reporting intention under reward model. This research applied the Reinforcement theory in designing whistleblowing policies. In this context, reward system in encouraging disclosure of fraudulent act was used. This study was designed using experiment method 2x2 between subjects with 86 participants from private universities. Sarbanes-Oxley Act of 2002 requires that every public company must establish anonymous channel regarding disclosure of fraudulent act. However, under the reward system it may become different prediction that non-anonymous channel is preferable than the other one. Using two types of fraudulent act, this research investigated whether those types affected individual’s intention for disclosing fraud in choosing the reporting channel because a reward is provided or not. The result shows that the interaction between the type of fraudulent act and type of channel could encourage individual’s intention to blow the whistle. However, individual prefers to report the misappropriation of asset through anonymous channel than non-anonymous even though a reward is provided.